The impact of technological innovations on employment in the financial sector - Palekhova, Viktoriya; Kramarenko, Olga (Technology audit and production reserves, 2020)
The object of research is the employment in the financial sector of three countries with different levels of development – the United Kingdom, South Korea, and Ukraine. It is well known that the current stage of the industrial revolution (“Industry 4.0”) is fundamentally different from previous ones, as it threatens the massive displacement of mental labor. This paper attempts to assess the impact of technological innovations on employment in the financial sector. Theoretical, statistical, and econometric methods are used in this research. The paper systemizes the various points of view on how the fourth industrial revolution may affect the labor market and attempts to test the validity of existing approaches. An analysis of the relationship between each country's level of technological development (which is measured by the Global innovation index) and the number of employees in the financial sector over the past seven years is conducted. A single-factor model is constructed for each country. Correlation and regression analysis prove the inverse relationship between the indicators in all countries: the higher the level of innovation, the lower the employment level. The results differ among countries only in terms of the strength of the relationship. The strongest relationship is found in South Korea, although the country is lower in the ranking of innovation potential and achievements compared to the United Kingdom. At the same time, South Korea is known as the world leader in terms of the number of robots per capita. However, the obtained results allow to state that there is a strong correlation between the two indicators in both developed countries. In Ukraine, there is a clear downward trend of employment in the financial sector, and the values of the Global innovation index are noticeably smaller and quite volatile. Econometric analysis shows that the relationship is also inverse, as in developed countries, but it is weaker. Therefore, the research results confirm the fears of those economists who extend the negative consequences of technological innovations to developing countries.